Imperative nostalgia: Russian science fiction novels about moving to the 1970s USSR - Koz'mina, Elena (Literatura Ludowa. Journal of Folklore and Popular Culture, 2023)
The article examines selected novels by Russian science fiction writers concerning the transition of heroes in the 1970s of the Soviet Union. These novels began being published quite recently, mostly by the authors themselves. The article formulates the differences between such works and similar fantastic historical novels: the hero’s arrival into his own era, the absence of the motive of “reviving history”, etc. The analysis of the novels allows us to conclude that this particular image of the bygone Soviet era is built by not only describing real historical events, but also using myths and stereotypes concerning the USSR. Nostalgia for late socialism permeates the novels, while calls for the restoration of the Soviet Union are already formulated in the very titles. Accordingly, another kind of nostalgia stands out – an imperative one with the following features: the absence of a utopian image of a bygone time; an active character, which makes the nostalgic feeling the opposite of the elegiac one. This imperative nostalgia based on myths and stereotypes is shared by readers who see Perestroika as a human catastrophe that destroyed the “wonderful world”. In addition, they are close to the conversational aggressive style with which the novels are written, as well as the image of a self-righteous hero. Imperative nostalgia reflects the needs for the restoration of the Soviet Union that have formed in modern society.